Seasonal effectiveness of a Korean traditional deciduous windbreak in reducing wind speed - Dowon Lee; Insu Koh; Chan-Ryul Park; Wanmo Kang (Journal of Ecology and Environment)
Little is known about how the increased porosity of a deciduous windbreak, which results from loss of leaves, influences wind speed reduction. We hypothesized that, with loss of foliage, the wind speed reduction effectiveness of a deciduous windbreak decreases on near leeward side but not on further leeward side and that wind speed recovers faster in the full foliage season than in other seasons. During summer, autumn, and winter (full, medium, and non- foliage season, respectively), we observed wind speed and direction around a deciduous windbreak in a traditional Korean village on windward and near and further leeward sides (at –8H, 2H, and 6H; H = 20 m, a windbreak height). We used a linear mixed effects model to determine that the relative wind speed reduction at 2H significantly decreased from 83% to 48% ( F 2,111.97 = 73.6, P < 0.0001) with the loss of foliage. However, the relative wind speed reduction at 6H significantly increased from 26% to 43% ( F 2,98.54 = 18.5, P < 0.0001). Consequently, wind speed recovery rate between 2H and 6H in summer was two times higher than in autumn and ten times higher than in winter ( F 2,102.93 = 223.1, P < 0.0001). These results indicate that deciduous windbreaks with full foliage seem to induce large turbulence and increase wind speed recovery rate on leeward side. Our study suggests that further research is needed to find the optimal foliage density of a deciduous windbreak for maximizing windbreak effectiveness regardless of seasonal foliage changes.